Back to Nature - Toga Menjadi Produk Olahan Herbal yang Bernilai Ekonomis - Wita Oileri Tikirik; Jesika Turuallo; Mardiana; Nurfaiga Maulani (Yayasan Literasi Sains Indonesia, 2022)
TOGA is one of the best options to deal with health problems independently at home without having to come to a health facility as well as an effort to reduce the use of chemical drugs by returning to nature (back to nature). TOGA is very much needed in the current COVID-19 pandemic situation in order to break the chain of transmission by staying at home. The target family has a large yard which is planted with several medicinal plants. They know what plants are used as medicine, but their utilization has not been optimally and correctly and they do not know how to process TOGA into products of high economic value. The purpose of this activity is to provide information and knowledge regarding the proper and correct use of TOGA and how to process it into powders and herbs. We are students of KKN STIKes Andini Persada Mamuju doing one of the program activities is processing TOGA. The processing stages of making TOGA are by cooking with several plants including, ginger, temulawak, lemongrass, turmeric, the advantage of this processing is to obtain products in the form of herbs and powders by cooking and brewing.